Respostas

2013-09-02T20:11:23-03:00
X+2y=5     (* -2)             x+2y=5     (* -3)       -5y +3z = -1   ( * - 9/5)
2x-y+3z=9                  3x-3y-2z =3               -9y-2z=-12
-----------------------      -------------------------         ----------------------
-2x-4y= -10                -3x-6y=-15                 9y - 27/5z = 9/5
2x-y   +3z=9               3x-3y-2z=3               -9y-2z=-12          > -9y- 2*1,36 = -12 > 
-----------------------    -----------------------------    ------------------------------    y=11,7
-5y +3z = -1                -9y-2z=-12                -7,5z = -10,2  > z = 1,36
1 1 1